The Role of Patient Satisfaction Mediation on Revisit Intention at Private Hospital During Covid-19 Pandemic - Krishanty Eka Putri; Tantri Yanuar Rahmat Syah (Budapest International Research and Critics University, 2022)
This study aims to confirm the previous theory regarding the positive influence of hospital service quality such as doctor service, nurses service, and waiting time on patient satisfaction. We made an update by making waiting time a moderator linking nurses' service to patient satisfaction, in addition, we added revisit intention as a result of the consequences of patient satisfaction. This research was conducted at a private hospital in Indonesia which includes 8 branches. The population of this study was obstetrics and gynecology poly patients who did self-financing. The method of determining the sample of this research is purposive sampling. Data collection is done online through the distribution of Google Form links on social media applications. Meanwhile, to process data and test hypotheses, this study uses dimensional reduction analysis methods and a structural equation model (SEM). The research process was carried out from September to December 2021. The results obtained in this study were doctor service and nurses service had a significant positive effect on patient satisfaction. Furthermore, waiting time is able to strengthen the influence of doctor' service on patient satisfaction. Lastly, patient satisfaction also has a significant positive effect on increasing revisit intention.